Expanding Judiciaries: India and the Rise of the Good Governance Court - Nick Robinson (Washington University Global Studies Law Review, 2009)
In recent years, courts have risen in power across the world, and the Indian Supreme Court has rightly been pointed to as an example of this global trend. In many ways the Indian Court has become a court of good governance that sits in judgment over the rest of the Indian government. This Article argues that the Court has expanded its mandate as a result of the shortcomings (real, perceived, or feared) of India's representative institutions. The Indian Supreme Court's institutional structure has also aided its rise and helps explain why the Court has gained more influence than most other judiciaries. This Article examines the development of India's basic structure doctrine and the Court's broad right to life jurisprudence to explore how the Court has enlarged its role. It argues that the Court justified these two doctrines with not only a wide reading of the Indian Constitution, but also an appeal to broad, almost metaphysical, principles of “civilization ” or good governance. The Article finishes by examining parallel interventions in other parts of the world, which suggest India's experience is part of and helps explain the larger global phenomenon of, the rise of rule through good governance principles via courts. Reprinted by permission of the publisher.
Keywords: Constitutional law – India; Rule of law; India. Supreme Court; Court administration; Judicial power; Judicial process; Judicial review; India